Albumin in the management of hepatic encephalopathy: A systematic review and meta-analysis - Bombassaro, Isadora Z.; Tovo, Cristiane V.; de Mattos, Ângelo Z.; Ahlert, Marcelo; Chiesa, Talita; de Mattos, Angelo A. (Annals of hepatology, 2021)
Introduction and objectives It has been suggested that albumin administration could alter the natural history of cirrhosis, and also, that long‐term treatment with albumin might be associated with improvement in survival, control of ascites, reduction in the incidence bacterial infections, renal dysfunction, hepatic encephalopathy (HE) and hyponatremia, as well as reduction in length of hospitalization in patients with cirrhosis and ascites. The objective of the present study is to evaluate the role of albumin in the management of HE. Materiales and methods:: This is a systematic review of randomized controlled trials that evaluated the use of albumin in adult patients with cirrhosis and HE. The search for eligible studies was performed in MEDLINE, EMBASE, and Cochrane CENTRAL databases until June 2020. The outcomes of interest were the complete reversal of HE and mortality. Meta‐analysis was performed using the random effects model, through the Mantel–Haenszel method. Results: This systematic review was registered at the PROSPERO platform (CRD42020194181). The search strategy retrieved 1,118 articles. After reviewing titles and abstracts, 24 studies were considered potentially eligible, but 22 were excluded after full-text analysis. Finally, 2 studies were included. In the meta-analysis, albumin was associated to significant lower risks of persistent HE (risk ratio – RR = 0.60; 95% confidence interval – CI = 0.38–0.95, p = 0.03) and mortality (RR = 0.54; 95% CI = 0.33–0.90, p = 0.02). Conclusion: Albumin administration improves HE and reduces mortality in patients with cirrhosis and HE.